A holistic and sustainable approach linked to drought tolerance of Mediterranean crops - Trovato, Maurizio; Brini, Faiçal; Mseddi, Khalil; Rhizopoulou, Sophia; Jones, Matthew Alan (Frontiers in Plant Science, 2023)
The rapid increase in average temperatures and the progressive reduction in rainfalls caused by climate change is reducing crop yields worldwide, particularly in regions with hot and semi-arid climates such as the Mediterranean area. In natural conditions, plants respond to environmental drought stress with diverse morphological, physiological, and biochemical adaptations in an attempt to escape, avoid, or tolerate drought stress. Among these adaptations to stress, the accumulation of abscisic acid (ABA) is of pivotal importance, and many biotechnological approaches to improve stress tolerance by increasing the exogenous or endogenous content of ABA have proved to be effective. However, in most cases the resultant drought tolerance is associated with low productivity incompatible with the requirements of modern agriculture. The on-going climate crisis has provoked the search for strategies to increase crop yield under warmer conditions. Several biotechnological strategies, such as the genetic improvement of crops or the generation of transgenic plants for genes involved in drought tolerance, have been attempted with unsatisfactory results suggesting the need for new approaches. Among these, the genetic modification of transcription factors or regulators of signaling cascades provide a promising alternative. To reconcile drought tolerance with crop yield, we propose mutagenesis of genes controlling key signaling components downstream of ABA accumulation in local landraces to modulate responses. We also discuss the advantages of tackling this challenge with a holistic approach involving different knowledge and perspectives, and the problem of distributing the selected lines at subsidized prices to guarantee their use by small family farms.